Halal food market potential and challenges faced by Malaysia in developing this sector - Mahadevan, Rajam (2011)
The halal food market is robust and growing at an exponentials rate. With 1.6 billion Muslims worldwide this sector cannot be ignored because of its increasing vibrance in recent years. Halal food sales alone have been valued at USD 580 billion annually. While Halal food meets with the religious requirement of Muslims as stated in the Quran, there are compelling facts make it not just permissible but also attractive to non-Muslim consumers, on the basis of scientific reason, hygiene, food safety and security. Greater marketing and communications efforts however, must be exerted by Halal food procedures to drive home this message. Malaysia’s Halal Certification and Branding efforts have gained ground overseas and has adopted as a guiding standard by some countries like Pakistan and Bangladesh. But sadly, Malaysian companies have not leveraged on this to gain a share of this large Halal pie. The government and its agencies have scored successes in this direction, while the private sector too has advance in some measure. But, there is a lot more that can and should be done to elevate our standing and leverage off the good reputation that Malaysia already holds within the GCC and OIC member countries. We are sandwiched between Singapore that’s moving fast in securing its food resources and Thailand that’s aiming to emerge among the top five global food producers soon. What is or vision, mission and game-plan in this arena?